Toxicidad de bioinsecticidas de origen vegetal en Brevicoryne brassicae y sus efectos en organismos no objetivos en condiciones de laboratorio - Diaz Landi, Diana Lizbeth (2023)
The cabbage aphid Brevicoryne brassicae (Hemiptera: Aphididae) is a key pest of cruciferous plants, causing direct damage by injecting toxins and continuously sucking sap, affecting plant development. To control and reduce the damage caused, synthetic insecticides are used; however, their use can put non-target organisms at risk, which justifies the search for control methods for this pest aphid. A sustainable tool for pest management is the use of biomolecules present in essential oils. Therefore, it is intended to identify the toxic activity of the essential oils of ishpingo (Ocotea quixos) and clove (Syzygium aromaticum) on Brevicoryne brassicae L. and evaluate the selectivity for two non-target organisms. For this purpose, a gas chromatography analysis was carried out, in which O. quixos chemically possesses (E)-β-Caryophyllene (19.32%), (E)-Cinnamyl acetate (17.11%), (E)- Methyl cinnamate (11.39%) as major compounds and Eugenol (75.28%), Eugenol acetate (15.62%) for S. aromaticum. The concentrations of the essential oils used were formulated in an aqueous solution with 2% distilled water, Dimethyl sulfoxide (DMSO) and Tween 20, and applied using a sprinkler. Mortality was evaluated after 24 hours of the oils exposure. The essential oils of Ocotea quixos LC50 = 12.20 (11.85 - 12.54) μl/ml and Syzygium aromaticum LC50 = 7.41 (6.77 - 8.08) μl/ml were toxic for B. brassicae. Both oils are moderately selective for Hippodamia convergens adults; however, in human HDFα cells the concentrations of O. quixos LC95 = 19.39 μl/ml and LC10 = 8.51 μl/ml are not selective. It is concluded that the tested products could be a tool for Integrated Pest Management to control aphids in horticultural crops. Keywords: bioinsecticides, Brevicoryne brassicae, gas chromatography, toxicity, non-target organisms.